Manipur Approach to Fifth Five Year Plan - Planning Commission (Planning Commission, 1974)
Long lines of communications and the lack of 1st clast road or rail communications within the State and connecting it to the neighbouring areas of the Indian Union have reflected detrimentally on the State's own economic development or rather the lack of it, and which in turn, is reflected in the isolated thinking and character of its people. the State is comparatively, perhaps, the least Integrated with the main-stream of the Indian Union administratively, politically, economically and socially.
Government of Manipur